pCRP-mCRP Dissociation Mechanisms as Potential Targets for the Development of Small-Molecule Anti-Inflammatory Chemotherapeutics - Caprio, Vittorio; Badimon, Lina; Di Napoli, Mario; Fang, Wen-Hui; Ferris, Glenn R.; Guo, Baoqiang; Iemma, Rocco S.; Liu, Donghui; Zeinolabediny, Yasmin; Slevin, Mark (Frontiers in Immunology, 2018)
Circulating C-reactive protein (CRP) is a key acute-phase protein and one of the main clinical biomarkers for chronic inflammation. CRP is an important upstream mediator of inflammation and is associated with the onset of a number of important disease states including cardiovascular disease and neurodegenerative disorders such as Alzheimer’s disease. This pentraxin exerts pro-inflammatory properties via dissociation of the pentamer (pCRP) to a monomeric form (mCRP). This dissociation is induced by binding of pCRP to cell surface phosphocholine residues exposed by the action of phospholipase A2 (PLA2). Given the association of CRP with the onset of a range of serious disease states this CRP dissociation process is a tempting drug target for the development of novel small molecule therapeutics. This review will discuss potential targets for chemotherapeutic intervention elucidated during studies of CRP-mediated inflammation and provide an up to date summary of the development of small molecules, not only targeted directly at inhibiting conversion of pCRP to mCRP, but also those developed for activity against PLA2, given the key role of this enzyme in the activation of CRP.